The Influence between Employee’s Trust and Attitude toward Organizational Change Mediated by Organizational Commitment to Employees of PT Transportasi Gas Indonesia - Achmad Nur Alamsyah; Riani Rachmawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Today's rapidly changing and complex business environment makes organizational changes common and inevitable as a company strategy to deal with change and to maintain business continuity, competitive advantage and organizational existence. Organizational change has an impact that can be felt by employees and raises various employee attitudes towards the changes that occur. With these conditions, this study wants to explore further how the attitude of employees towards change with a number of factors or variables that influence employee attitudes towards change, namely the factor of trust (trust in the organization and trust in supervisors) and organizational commitment. The research was conducted on organic employees of PT TGI as respondents by distributing questionnaires as a data collection method. Questionnaire data processing analysis used structural equation modeling to determine the effect of employee's trust and attitude toward organizational change using organizational commitment as a mediator. The results showed that the direct relationship between employee's trust (trust in organization and trust in supervisor) on attitude toward organizational change was significant positive. Meanwhile, through organizational commitment, the indirect effect of employee trust on attitudes toward organizational change is also positive and significant.